Metodologia baseada em simulações para determinação dos esforços eletromecânicos em transformadores de potência - Medeiros, Leonardo Hautrive (2020)
The power transformers, responsible for adapt the voltage levels, are essential equipment to the operation of electrical systems. Exposed to different situation, they are subject to several failures that can lead to an operational unavailability. Among the failures, there may be the rupture of the dielectric insulation, due the windings deformations by electromechanical forces from high currents, as short-circuits, leading to technical and financial losses. This master thesis presents a methodology for electromechanical forces determination and its distribution in the windings through simulations employing Finite Element Method. After an overview of the forces, presenting operating situations of high currents and possible deformations, analytical methods of calculation are approached, exposing their simplifications and applications difficulties, with the example of the use Waters’ equations on three concentric windings arrangements: same height, tap on the end of winding and central tap. Thereby, 3D modeling and simulations of the same arrangements in finite element software are presented, showing the practicality and applicability of the simulation method. After comparing the simulations results with the equations, analyzes of the radial and axial forces are presented, with details in divisions modeled along the height of the windings and around the core column, including a parametric variation in the tap size. From the simulations, it was found that the analytical equations, even with simplifications, are accurate. Additionally, the finite element simulation tool proved to be very efficient, mainly because it allows the modeling and analysis of more complex geometries and arrangements, where the equations applications becomes limited. Still, with simulation modeling, the forces distribution was verified in detail, in addition to critical points and characteristics that can be taken into account I more reliable transformers projects.